Process evaluation of the ‘Singapore Physical Activity and Nutrition Study - Wong, Elaine Yee-Sing; Lee, Andy; James, Anthony; Jancey, Jonine (Elsevier, 2020)
Introduction: The Singapore Physical Activity and Nutrition Study (SPANS) aimed to improve the physical activity (PA) and nutrition behaviours of Singaporean women aged 50 years and over. The SPANS program consisted of PA classes, nutrition workshops, telephone dietary counselling, health booklets, a health calendar and program ambassadors. This study aimed to assess and understand the implementation of the program strategies and gain insight into process evaluation components to inform future programs.